Deconstruction and Reuse of Building Material, with Specific Reference to Historic Structures - Whyte, Andrew; Laing, Richard (Research Publishing Services, 2012)
The planned deconstruction of built assets (literally taking buildings apart for maintenance, refurbishment, retrofitting or demolition purposes) has taken on increasing importance in recent years, due to the finite nature of raw materials, respective cost increases and a desire to recognise environmental imperatives. It is argued that best practicable environmental (& financial) options for the waste-management of building-maintenance and demolition arisings can be identified. The focus of this paper is on the deconstruction of listed/historic buildings and historic town centre maintenance. Material scarcity juxtaposed with a reduced availability of skilled trades-people is likely to have an effect on the condition and appearance of urban centres in the future. If regional variation in material quality, characteristic and aesthetic is deemed important, then the development of a sound pragmatic approach to deconstruction within historic locations is needed to ensure a continuity between, on the one hand, the architecture of the past, and on the other hand, new development essential to the continued vitality of urban areas. Work described here finds that the deconstruction process of listed built assets must integrate the design of new work, with, specifications that stipulate both the use of recyclates and, indicate where these recycled materials may be obtained. It is recommended that such a structured approach for historic-buildings/historic-areas will makes a genuine contribution to the upkeep our built heritage.